NIDHAL GUESSOUM DAN ALTERNATIF PERKEMBANGAN SAINS ISLAM - Abdullah Hanif (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2018)
Science in Islam is indeed not a new thing, by the meaning as a scientific tendency. In histories, science is like to be a western thing, although so many early Islamic scholars do scientific research and even be a reference for some western scholars. However in the essence of the science, Islam had made his own long history, where some Islamic scholars took a specialization in the science as a world outside the religion, and some other Islamic scholars made a construction that science should be in a same voice as religion. This lifetime history and debate have been written by Nidhal Guessoum in an objective alternative that multilevel paradigm is believed as a main base could be used by Islamic scholars in many aspects to develop a theistic science – which is a form of science that believed to have a bigger opportunity to be developed in the Islamic world. With this multilevel paradigm, he tried to exclude science out of his specific perceptions towards natural sciences, to be returned to its scientific and rational epistemological form.